(3Mbhb GdEfSGf (B:s (3OQGSI ebGQfI Hjf GdbGfhf GdCQOfj hGdehGKjb GdOhdjI (B/s - (3GdHTjQ, SYO Ydjs ((3YeGf(B: s (3OGQ QhGFY eLOdGhi(B, s, 2002)
(3Mbhb GdEfSGf aj GdTQYjI GdOhdjI(B- (3Mbhb GdEfSGf Ydi GdeSJhi GdEbdjej(B- (3Mbhb GdEfSGf Ydi GdUYjO GdhWfj (B((3Mbhb GdEfSGf hMQjGJg aj GdeedcI GdCQOfjI GdgGTejI(B)- (3GdbhGYO GdfehPLjI GdOfjG dMbhb GdEfSGf aj eYGedI GdSLfGA(B- (3GdELQGAGJ GdYedjI GdaYdjI GdJj GJNPgG GdCQOf aj eLGd GdeHGOF SGdaI GdPcQ Gdi MjR GdJfajP(B- (3QO GdMcheI Ydi JbQjQ hRGQI GdNGQLjI GdCeQjcjIs
Keywords: (3GdbGfhf GdOhdjs; (3Mbhb GdEfSGfs